Implication-based neuro-fuzzy architectures - Rutkowska, Danuta; Nowicki, Robert K. (Zielona Góra: Uniwersytet Zielonogórski)
This paper presents connectionist multi-layer architectures of neuro-fuzzy systems based on various fuzzy implications. The well-known Mamdani approach (constructive) and the logical approach (destructive) are considered. Two kinds of architectures, a simpler and a more general one, are distinguished. Examples of application to classification and control problems are provided.
Keywords: neuro-fuzzy systems; fuzzy implications; fuzzy inference; Mamdani approach; logical approach; connectionist architectures